Fish gut microbiome and its application in aquaculture and biological conservation - Kanika, Nusrat Hasan; Liaqat, Nusrat; Chen, Huifan; Ke, Jing; Lu, Guoqing; Wang, Jun; Wang, Chenghui (Frontiers in Microbiology, 2025)
Understanding the diversity and function of fish gut microbiomes has advanced substantially, yet many aspects remain poorly understood, particularly the interplay among microbiota, host species, and environmental factors in the context of conservation. This review explores the composition and abundance of gut bacterial communities in key aquaculture fish groups—cyprinids, ictalurids (catfish), salmonids, and cichlids (tilapia)—alongside the model organism zebrafish, across diverse geographic regions. The findings highlight environmental habitats and host species as primary determinants of gut microbiome structure, offering a global perspective on these microbial communities. Across all fish groups, the phyla Firmicutes, Fusobacteria, and Proteobacteria consistently dominated, while temperate, sub-equatorial, and sub-tropical regions exhibited the highest microbiome diversity, underscoring the contribution of taxonomic and environmental factors. The gut bacterial diversity of farm-raised fish shows a significant divergence from that of wild-caught fish, reflecting the impacts of ecological and management differences. Understanding the dynamic responses of fish gut microbiota is vital for guiding conservation efforts, safeguarding aquatic biodiversity, and advancing sustainable aquaculture practices. Future research should leverage innovative techniques and integrative approaches, both experimental and theoretical, to uncover the functional roles of microbiomes and predict their responses to environmental changes. Expanding geographic and taxonomic coverage will be critical for creating a comprehensive framework to inform global aquaculture and conservation strategies. Collectively, this perspective highlights the transformative potential of microbiome research in addressing global challenges in aquaculture and conservation biology.